Advances in Research Into and Applications of Heterotrophic Nitrifying and Aerobic Denitrifying Microorganisms - Fu, Weilai; Song, Guolong; Wang, Yunshuang; Wang, Qiang; Duan, Peifeng; Liu, Chao; Zhang, Xian; Rao, Zhiming (Frontiers in Environmental Science, 2022)
With the increasing use of animal and plant proteins, pollution due to nitrogen sources is attracting increasing attention. In particular, the amount of nitrogen-containing sewage discharged into the environment has increased significantly, causing eutrophication of water bodies and environmental degradation of water quality. Traditionally, nitrifying bacteria perform ammonia nitrification under aerobic conditions, while denitrifying bacteria perform nitrate/nitrite denitrification under anaerobic conditions. However, heterotrophic nitrifying and aerobic denitrifying microorganisms (HNADs) perform ammonia nitrification and nitrate/nitrite denitrification under the same aerobic conditions using an organic carbon source, which is a much simpler and more efficient process. In this review, the distribution and evolutionary relationships of novel HNADs strains are presented, and the influencing factors, metabolic pathways, key enzymes, and practical applications of HNADs are reviewed.